ChemInform Abstract: FeSO4·7H2O‐Catalyzed Oxidative Amidation of Methylarenes. Issue 36 (September 2015) - Karimi, Meghdad; Saberi, Dariush; Azizi, Kobra; Ghonchepour, Ehsan; Heydari, Akbar
Abstract Optimized conditions render possible the synthesis of primary, secondary, and tertiary amides from methylarenes and amine hydrochlorides.